TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PENCEMARAN NAMA BAIK MELALUI MEDIA SOSIAL - Dwi Oktafia Ariyanti (Kajian Hukum, 2017)
The Development of information technology influences social changes that are significant and take place so fast. Currently information technology in addition to contributing to the advancement of human civilization is also at once a means that can lead to unlawful acts. Currently information technology in addition to contributing to the advancement of human civilization is also at once a means that can lead to unlawful acts. Under these conditions vulnerable violations of defamation and defamatioan through social media, as people often misuse their freedom of expression. This research is conducted by using the normative juridical approach is the approach done based on the main legal material by studying the theories, concepts, legal principles and legislation related to this research. This approach is also known as the literature approach, by studying books, legislation and other documents relating to this research.The regulation on defation trough social media in act number 19 of 2016 concerning amendment to law number 11 year 2008 concerning information and electronic transactions is contained in article 27 paragraph (3) and article 45 paragraph (3) and paragraph (5). In article 27 paragraph (3) regulaties the prohibited act which is categorized in the offense of defamation or defamation while in article 45 regulates the criminal provisions. Law number 19 year 2016 on amandement to law number 11 year 2008 on information and electronic transactions does not stipulate restriction on opinion trough social media that may cteate muliple interpretations. Judging from the type of punishment is possible for the existence of alternative types of criminal other than imprisonment, namely social work crime and criminal supervision. Both types of crime are considered more effective and provide prospects of coaching so that the purpose of criminal punishment in the form of community protection and protection of onvicts can be achieved.Keywords : Yuridical Review, criminal defamation, social media